A Medicago truncatula HD-ZIP gene MtHB2 is involved in modulation of root development by regulating auxin response - Yan, Wei; Wang, Runze; Zhang, Yutong; Zhang, Xiuxiu; Wang, Qin (Frontiers in Plant Science, 2024)
HD-Zip proteins are plant-specific transcription factors known for their diverse functions in regulating plant growth, development, and responses to environmental stresses. Among the Medicago truncatula HD-Zip II genes, MtHB2 has been previously linked to abiotic stress responses. In this study, we conducted a functional characterization of MtHB2 in the regulation of root growth and development. Upon auxin stimulation, expression of MtHB2 was promptly up-regulated. Overexpression of MtHB2 in Arabidopsis thaliana led to reduced primary root growth and inhibited lateral root formation. Interestingly, the transgenic plants expressing MtHB2 exhibited differential responses to three types of auxins (IAA, NAA, and 2,4-D) in terms of root growth and development compared to the wild-type plants. Specifically, primary root growth was less affected, and lateral root formation was enhanced in the transgenic plants when exposed to auxins. This differential response suggests a potential role for MtHB2 in modulating auxin transport and accumulation, as evidenced by the reduced sensitivity of the transgenic plants to the auxin transport inhibitor NPA and lower expression levels of auxin-related reporters such as PIN-FORMED (PIN1)::PIN1-GFP,